2019
DOI: 10.1037/tps0000187
|View full text |Cite
|
Sign up to set email alerts
|

Is immigration a culture? A qualitative approach to exploring immigrant student experiences within the United States.

Abstract: The present study investigated the lived immigration experiences of 10 students enrolled in or graduated from a university (i.e., bachelor's degree) in the United States using a phenomenological approach. Participants represented 9 different countries, cultures of origin or backgrounds, and self-identified as either immigrant or firstgeneration American. The present research contributes to current literature by exploring the experiences of immigrants across ethnicities and cultures of origin. After survey comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Sixteen second-generation American undergraduate ( n =13) or graduate ( n =3) students at the University of Nevada, Reno participated in this study. Initially, participant recruitment was guided by examining similar studies with second-generation college student participants, which have had 5–15 participants (Brady and Stevens 2019 ; Eaton 2006 ; Morales 2012 ; Muñoz 2012 ; Schackmuth 2012 ; Skulley 2004 ). To uphold data saturation principles in qualitative research, the first author concluded the study after 16 interviews as new data did not provide added information (Glaser and Strauss 1967 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sixteen second-generation American undergraduate ( n =13) or graduate ( n =3) students at the University of Nevada, Reno participated in this study. Initially, participant recruitment was guided by examining similar studies with second-generation college student participants, which have had 5–15 participants (Brady and Stevens 2019 ; Eaton 2006 ; Morales 2012 ; Muñoz 2012 ; Schackmuth 2012 ; Skulley 2004 ). To uphold data saturation principles in qualitative research, the first author concluded the study after 16 interviews as new data did not provide added information (Glaser and Strauss 1967 ).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, they take up the challenges of adaptation facing unaccompanied immigrant minors (Alvarez, NeMoyer, & Rodriguez, 2019), the experiences of Syrian refugee caregivers and children in perimigration (the period between displacement and resettlement; Watamura, Miles, & Narayan, 2019), and the nature of the association between receiving community context and acculturative stress among Latina young adult immigrants (Verile, Ertl, Dillon, & De La Rosa, 2019). Another article focuses on the experiences and needs of immigrant college students from nine different countries (Brady & Stevens, 2019) and asks a provocative question about whether immigration experience itself can be considered a unique cultural experience. Other articles showcase the utility of community-based research and partnerships to implement an intervention to reduce stress among Latinx immigrants (Vaughn, Jacquez, & Suarez-Cano, 2019), to explore the relationship of Latinx parents’ concerns about their documentation status with involvement in their children’s schools (Cross et al, 2019), and to engage Chinese immigrant breast cancer survivors into a randomized control intervention trial (Wu et al, 2019).…”
Section: Translational Issues In Psychological Sciencementioning
confidence: 99%
“…Beyond cultural differences and migratory status, first‐ and second‐generation adolescents from different cultures of origin experience similarities in their migration process and their acculturation efforts (Berry, 2005; Brady & Stevens, 2019). Moreover, in Canada and the United States, there is a dominant culture, and adapting to it represents a more or less important stressor for foreign‐born youth or children of immigrants (Roysircar‐Sodowsky & Frey, 2003).…”
Section: Introductionmentioning
confidence: 99%